Isolation, Identification, and Antibiotics Resistance of Aeromonas spp. from Lakes of Udaipur (Rajasthan), India - Joshi, H. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: Aeromonas spp. are commonly found in freshwater ecosystems. Aeromonas is Gram-negative, facultative anaerobes which causes aeromonasis in humans and are also pathogenic for aquatic and terrestrial animals. In this study, an attempt has been made to isolate Aeromonas spp. from lakes of Udaipur, namely, Fateh Sagar and Pichhola and to test their antibiotic resistance. Materials and Methods: The isolates were recovered on nutrient agar medium and screened for their growth on Aeromonas selective agar medium. Selected isolates were subjected to biochemical characterization. For molecular characterization, genomic DNA of all the isolates was amplified using universal primers 27 F and 1492 R, and amplified products were subjected for sequencing to confirm their identification. The isolates were tested for antibiotic resistance against 15 commonly used antibiotics, i.e., gentamycin, kanamycin, tetracycline, erythromycin, ampicillin, penicillin, polymyxin B, amikacin, ciprofloxacin, vancomycin, rifampicin, chloramphenicol, streptomycin, cefixime, and trimethoprim by disc diffusion method. Results and Discussion: Out of 116 isolates, a total of 14 strains able to grow on Aeromonas selective agar medium were selected. They were identified and grouped into 2 species as Aeromonas veronii and Aeromonas hydrophila according to their biochemical and molecular characteristics. All the strains, which were identified as A. veronii, were found resistant to 8 antibiotics, namely, AMP, penicillin, VA, kanamycin, polymyxin B, rifampicin, erythromycin, and streptomycin. All the strains, which were identified as A. hydrophila, were found resistant to 10 antibiotics, namely, ampicillin, penicillin, vancomycin, kanamycin, polymyxin B, rifampicin, erythromycin, streptomycin amikacin, and trimethoprim out of 15 antibiotics used in the study. Conclusion: The results indicated that the water of both the lakes was contaminated with multi-antibiotic-resistant enteric pathogenic bacteria. This study thus provides valuable information for making policy decisions aimed at reducing microbial contamination of lake water and the indiscriminate use of antibiotics.